Renato Rizzi - La Cattedrale di Solomon a Lampedusa - Pisciella, Susanna (Firenze Architettura, 2018)
The Cathedral of Solomon is the negative of the traditional idea of a cathedral. It is not a majestic architectural mass, but rather a majestic cavity. Not the most panoramic spot on the island, but its most hidden cave, ideal for constructing its interior landscape. Lampedusa itself becomes architecture. Its interior is emptied and its rocky body opens to receive the barges which arrive from Africa. An enormous arc of safety awaiting alone in the middle of the Mediterranean. The project highlights three points: the singularity of the island, the singularity of the work, and the singularity of the soul.